The effect of Acacia senegal as potential prebiotic on obese gut microbiota - Sarbini, Shahrul Razid (Rynnye Lyan Resources, 2020)
Gut microbiota is able to affect body weight by fermenting dried fibers and generating short chain fatty acids (SCFA). Acacia senegal is an edible dried which might have potential prebiotic activity. The aim of this study was to investigate the effect of Acacia senegal as potential prebiotic on the composition and activity of human colonic microbiota of obese healthy subjects. In order to identify a potential prebiotic effect of Acacia senegal on obese individuals, anaerobic, pH-controlled batch cultures system was applied. The growth of different microbes and the concentration of lactic acid and short chain fatty acids were studied at 0, 6, 12, 24 and 36 hrs using fluorescent in situ hybridization (FISH) and HPLC respectively. The results showed that Acacia senegal was able to simulate the microbiota population since it significantly increased (P>0.05) the population of Bifidobacterium and decreased the population of Clostridium. Moreover, the supplement of Acacia senegal to the models significantly modulate short-chain fatty acid concentration. These findings clearly identified Acacia senegal as an additional contributing factor to the gut microbiota of obese subject and suggest that Acacia senegal could be an interesting supplement for obese human which might help to control obesity.